1988
DOI: 10.1007/bf00007931
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of deepwater rice-fields in Bangladesh 3. Associated algae and macrophytes

Abstract: i) Aquatic macrophytes formed dense beds in fallow areas during the four and a half months of the flood season in all but one deepwater rice-growing location in Bangladesh; these included several types of life-form, but the fine-leaved species, Mpophyllum sp., Najas indica, Utricularia stellaris were often especially abundant. The same species grew inside deepwater rice fields, but at much lower densities. A similar contrast occurred for the algae, although deepwater rice often developed dense masses of epiphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 7 publications
(11 reference statements)
0
31
0
Order By: Relevance
“…Cyanobacteria are known to inhabit a range of habitats, including plant surfaces [4][5][6], but this has not been adequately explored for improving their biofertilizing potential in agriculture and the rhizosphere is a relatively unexplored frontier. Watanabe and co-workers [7] observed that the associative nitrogen fi xation of the rhizosphere was too low to meet the nitrogen demand of rice crop.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria are known to inhabit a range of habitats, including plant surfaces [4][5][6], but this has not been adequately explored for improving their biofertilizing potential in agriculture and the rhizosphere is a relatively unexplored frontier. Watanabe and co-workers [7] observed that the associative nitrogen fi xation of the rhizosphere was too low to meet the nitrogen demand of rice crop.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on epiphytic cyanobacteria in rice fields have been performed only in deep-water rice fields, where these organisms are associated with deep-water rice tillers (2,34,35). In shallow-water rice fields only benthic and planktonic communities have been considered (14,20,27).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies has shown that even the cyanobacteria mainly Nostoc and Anabaena were found to be capable of forming associations with wheat roots grown in liquid culture [22]. In recent years, evidence is accumulating on the production of signals by the cyanobionts, which affects the gene expression of the host plants, and thereby brings about qualitative and quantitative changes in the soil micro flora in the rhizosphere [31,32,76].…”
Section: Distribution Of Cyanobacteriamentioning
confidence: 99%
“…Most of the works related to cyanobacterial biofertilizers have been in relation to rice crop, and few reports are available on epiphytic growth of Gleotrichia pisum on the aquatic roots/stem of deep water rice [76]. Cocultivation of wheat with cyanobacteria is known to enhance root dry weight and chlorophyll [35].…”
Section: Heterotrophic Contributionsmentioning
confidence: 99%